2022
DOI: 10.7554/elife.68040
|View full text |Cite
|
Sign up to set email alerts
|

Impairing one sensory modality enhances another by reconfiguring peptidergic signalling in Caenorhabditis elegans

Abstract: Animals that lose one sensory modality often show augmented responses to other sensory inputs. The mechanisms underpinning this cross-modal plasticity are poorly understood. We probe such mechanisms by performing a forward genetic screen for mutants with enhanced O2 perception in Caenorhabditis elegans. Multiple mutants exhibiting increased O2 responsiveness concomitantly show defects in other sensory responses. One mutant, qui-1, defective in a conserved NACHT/WD40 protein, abolishes pheromone-evoked Ca2+ res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…15 To determine whether the glial response to cilia defects can also follow acute cilia perturbation, we designed an inducible cilia degradation system. Briefly, sequences encoding AID, an a uxin-inducible d egron, 30,31 were introduced into the genomic osm-6 locus of animals also ubiquitously expressing the AID-targeting scaffold protein TIR1 ( eft-3pro::TIR1-mRuby ; Figure 2A ; a related method is described in 32 ). While control animals carrying either osm-6::AID or eft-3pro::TIR1-mRuby , have no dye-filling defects, we found that in the majority of animals carrying both constructs, sensory neurons become dye-filling defective within 1.5 hours of auxin exposure ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 To determine whether the glial response to cilia defects can also follow acute cilia perturbation, we designed an inducible cilia degradation system. Briefly, sequences encoding AID, an a uxin-inducible d egron, 30,31 were introduced into the genomic osm-6 locus of animals also ubiquitously expressing the AID-targeting scaffold protein TIR1 ( eft-3pro::TIR1-mRuby ; Figure 2A ; a related method is described in 32 ). While control animals carrying either osm-6::AID or eft-3pro::TIR1-mRuby , have no dye-filling defects, we found that in the majority of animals carrying both constructs, sensory neurons become dye-filling defective within 1.5 hours of auxin exposure ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…15 To determine whether the glial response to cilia defects can also follow acute cilia perturbation, we designed an inducible cilia degradation system. Briefly, sequences encoding AID, an auxin-inducible degron, 30,31 were introduced into the genomic osm-6 locus of animals also ubiquitously expressing the AID-targeting scaffold protein TIR1 (eft-3pro::TIR1-mRuby; Figure 2A; a related method is described in 32 ).…”
Section: The Amsh Glia Response To Cilia Disruption Is Acutementioning
confidence: 99%
“…LURY-1 peptides are cognate ligands of the luqin-like receptor NPR-22/LUQR-1 and are the most potent ligands of this receptor in vitro ( Beets et al, 2023 ; Gadenne et al, 2022 ; Mertens et al, 2006 ; Ohno et al, 2017 ). Initially, LUQR-1 was described as a tachykinin-like receptor with roles in fat metabolism, sleep promotion, and control of neurosecretion in ADL neurons ( Keating et al, 2003 ; Palamiuc et al, 2017 ; Turek et al, 2016 ; Valperga and de Bono, 2022 ). Further phylogenetic analysis established LUQR-1 as an ortholog of the luqin/RYamide receptor family ancestral to bilaterian animals ( Beets et al, 2023 ; Jékely, 2013 ; Mirabeau and Joly, 2013 ; Ohno et al, 2017 ).…”
Section: Conservation Of Ancestral Peptidergic Signaling Systems In ...mentioning
confidence: 99%
“…Genes in the “Signal transduction” category were filtered by the gene ontology term “signal transduction” – GO:0007165. The categories “Transcription factors” and “Neuropeptides” were derived from a curated list of C. elegans transcription factors and neuronal genes (Hobert, 2013; Valperga and de Bono, 2022).…”
Section: Figure S1mentioning
confidence: 99%
“… C) Enriched neuronal gene classes from temperature-dependent genes in AFD and whole animal samples using clusterProfiler (Yu et al, 2012) on curated C. elegans neuronal genes (Hobert, 2013; Valperga and de Bono, 2022). …”
Section: Figure S1mentioning
confidence: 99%